Geology, Geochemistry and Some Genetic Discussion of The IIC Anomaly, Bafq Ditrict, Central Iran (Revista Geoaraguaia, 2021)
Zaqia IIC anomaly is located in the east of Bafq city in Yazd province. Alteration associated with mineralization has appeared within volcanic, intrusive and sedimentary rocks. The set of alterations of this anomaly consist potassium, sericitic and silicate alterations, with less sodic-calcic alterations. Iron minerals are observed in the form of veins and masses with various compositions in this deposit. Iron ore in Zaqia IIC anomaly is related to magma and hydrothermal fluids. A collection of accumulated zones is composed of high-temperature minerals at depth to subvolcanic assemblages on the surface. REE patterns in iron ores in IIC anomalies indicate LREE enrichment and Eu negative anomaly. The negative Eu anomaly shows the reducing conditions of the mineralizing fluid. Isotopic studies have been conducted to examine the source of the fluid. The mineralizing fluid source in this anomaly is sedimentary-metamorphism. Field observations, mineralogy, alterations along with ore geochemical data show that a magmatic fluid is turned to an iron-rich brine fluid; moreover, an IIC anomaly is formed.